Education FAQ

(3√5-√11)(4+2√11) How To Simplify This Radical?
Use the distributive property. (3√5 - √11)(4 + 2√11) = 3√5(4 + 2√11) - √11(4 + 2√11) = 12√5 + 6√55 - 4√11 - 22 I wouldn't say this is much simpler.

(-4)(-4) To The -2 Power, Can You Help?
(-4)(-4) -2 = (-4)/(-4) 2 = -4/16 = -1/4 Per the order of operations, the term next to the exponent is evaluated first.

(-4,-1),(-2,-5) Find The Slope Of The Line That Passes Through Each...
The slope of line through two points is; m=(y2-y1)/(x2-x1) let (x1,y1)= (-2,-5) and (x2,y2)=(-4,-1) So, m=(-1+5)/(-4+2) m=4/ -2 m=-2

(400,000-600,000)/600,000 / (16,500-13,500)/13,500?
I need to figure out the answer By simplyfying the about cross-question we will get the following; =-200000/600000/3000/13500 =-.33333/.22222 =-1.5 is the answer.

(5d) For D = 8, Please Can You Help Me?
Please help me I'm a little rusty in my algebra but I believe (5d) when d=8 would be 5xd or 5x8 which is 40. Thank you VERY MUCH !! i SPENT ALL MY WEEKEND TRYING TO FIGURE IT OUT!!

(5x+1)^2=36, Solve The Equation?
Solve the equation? Take the square root and solve for x. (5x+1) = ±6 Let's do -6 first 5x + 1 = -6 5x = -7 x = -7/5 Now for +6 5x + 1 = 6 5x = 5 x = 1 That's a bit excessive and...

(5x-1)(3x-2) Use FOIL To Multiply, Can You Please Solve This Problem?...
Please solve this problem (5x - 1)(3x - 2) = 5x(3x - 2) - (3x - 2) 15x 2 - 10x - 3x - 2 = 15x 2 - 13x - 2 (3x2 + 3) - (6x + 4) + (3x2 - 5x)

(-7,5); 3x + Y < -6 How Would You Determine If The Ordered Pair Is...
Try it out. 3(-7) + (5) ?< -6 -21 + 5 ?< -6 -16 < -6 The point (-7, 5) is in the solution set of the given inequality. Is that how it will always work...

(7x^2 - X + 1) - (2x^2-x-3) - (5x^2 +3x -10), Can You Perform The...
Perform the indicated operations For this question u have to group similar to terms...that is add x 2 together and attach x's together so you'll get 7x 2 - x + 1 - 2x 2 + x + 3...

(7x^2-x+1)-(2x^2-x-3)-(5x^2+3x-10), Can You Help?
(7x^2-x+1)-(2x^2-x-3)-(5x^2+3x-10) = x 2 (7-2-5) + x(-1-(-1)-3) + (1-(-3)-(-10)) = 0x 2 - 3x + 14 = 14 - 3x.

-(7x+7)=1+4(x+9),how To Solve?
Our question is: -(7x+7)=1+4(x+9) Expanding: -7x-7=1+4x+36 Shifting all the x values on the right hand side and adjectives the other on the left hand side. Hence: -7x-4x=1+36+7 Solving: -11x=44 dividing: -x=44/11 -x=4 multiplying both sides by -1: -1*-x=4*-1 So: x=-4 So our value of x is -4

(7x-5)(9x-3),Can You Tell Me?
Ok.....I have no idea what that is supposed to connote and how those numbers were attained. 7X...7 times an unknown(X) -5 times 9 times X(unknown) minus 3......OK.....'splain that in English please. PS: What is the point? What are you trying to figure?? (7X-5) (9X-3) (7X * 9X) + (7X * -3) -(5...

(8 1/2)2=?
(8 1/2) 2= The solution to your math problem (8 1/2) 2 is 17.First make the mixed number "8 1/2 " in to a fraction which equals 17/2 and after that the 2 outside the bracket cancels out this 2 so merely 17 remains.

(-8x^5)(-4x^9),Can You Help Me?
When two algebraic entities are multiplied their coefficients are added to yield a result, provided that the base is the same entity. In this crust the result would be :- (-8x^5)(-4x^9) => 40x^(5+9) => 40x^14

(-8x^5)(-4x^9),Can You Help?
(-8x^5)(-4x^9) = (-8x 5 )(-4x 9 ) = (-8)(-4)(x 5 .x 9 ) = 32x 5+9 = 32x 14

(9D2-12D+4)y=0, Can You Solve The Following Differentials?
Solve the following differentials The characteristic equation is 9D 2 -12D+4=0 (3D-2) 2 =0 D= 2/3, 2/3 The general solution is y=(c1+c2x)e 2/3 x

(a + B)2 ≠ A2 + B2. Can You Give A Numerical Example To Illustrate...
This question means that when a sum of two numbers is squared the answer is NOT equal to the other side where both the numbers are squared and next added. Let's put in a number into this equation:...

(A+B+C)' = A'B'C' Using Truth Table?
(A+B+C)' = A'B'C' using truth table A B C (A+B+C) (A+B+C)' A' B' C' A'B'C' 0 0 0 0 1 1 1 1 1 1 0 0 1 0 0 1 1 0 1 1 0 1 0 0 0 1 0 1 0 1 1 0 0 1 0 0 0 0 1 1 0 1 1 0 0 0 1 1 1 0 1 0 0 0 1 1 1 1 0 0 0 0 0 HOPE THIS HELPS (A+B+C')(A'+B'+C)= A + B+(A +...

(Compound Annuity) What Is The Accumulated Sum Of Each Of The Following...
If the annuity is an "annuity due," that is, one with the payment made at the initiation of the period, the accumulated value at the winding up of the final period is A = P((1+i) n -1)(1+i)/i = $500((1.05) 10 -1)(1.05)/.05 =...

(csc^2(x)) / (cot(x)) = Sec(x)*csc(x)?
I can't seem to be able to solve this correctly, please help.... (csc^2(x)) / (cot(x)) = Sec(x)*csc(x) Taking disappeared hand side (Cosec^2 x) / (Cot x) -------- (a) Cosec x= 1/ Sin x Cot x= Cos x/ Sin x Put values of Cosec x and...